Molybdenum disulphide lubrication - Lansdown, A. R. (Tribology series, 1999)
In the 1970s and the early 1980s there was an enormous volume of research and development into the subject of molybdenum disulphide lubrication, much of which was supported by national governments for the benefit of defence, aviation or space activities.